Bile acids induce activation of alveolar epithelial cells and lung fibroblasts through farnesoid X receptor‐dependent and independent pathways. Issue 6 (17th May 2016) - Chen, Bi; Cai, Hou‐Rong; Xue, Shan; You, Wen‐Jie; Liu, Bin; Jiang, Han‐Dong
Abstract: Background and objective: The roles of bile acid microaspiration and bile acid‐activated farnesoid X receptor (FXR) in the pathogenesis of idiopathic pulmonary fibrosis (IPF) remain unclear. We hypothesized that bile acids activate alveolar epithelial cells (AECs) and lung fibroblasts, which may be regulated by FXR activation. Methods: Human AECs and normal or IPF‐derived lung fibroblast cells were incubated with the three major bile acids: lithocholic acid (LCA), deoxycholic acid (DCA) and chenodeoxycholic acid (CDCA). The AECs injury indices, epithelial‐mesenchymal transition (EMT) and lung fibroblast activation were evaluated. FXR expression in IPF lungs and the roles of FXR and FXR‐independent pathways in bile acid‐induced profibrotic effects were also investigated. Results: LCA, DCA and CDCA reduced cell viability and increased intracellular reactive oxygen species (ROS) production in A549 cells. They all induced EMT, as shown by enhanced α‐SMA and vimentin and decreased E‐cadherin levels. LCA directly induced differentiation of lung fibroblasts to myofibroblasts. All three bile acids promoted cellular migration but not proliferation of lung fibroblasts. FXR expression was upregulated in IPF lungs, and inhibition of FXR restrained the bile acid‐induced EMT and lung fibroblast activation. Differentiation and proliferation were enhanced in lung fibroblasts exposed to conditioned medium from bile acid‐stimulated A549 cells, which contained increased levels of profibrotic factors. TGF‐β/Smad3 signaling was also involved in the bile acid‐induced EMT and lung fibroblast differentiation. Conclusion: Bile acid microaspiration may promote the development of pulmonary fibrosis by inducing activation of AECs and lung fibroblasts via FXR‐dependent and independent pathways. Abstract : This study explores the role of bile acid microaspiration and Farnesoid X receptor (FXR) activation in the pathogenesis of idiopathic pulmonary fibrosis and demonstrates that bile acids could induce activation of alveolar epithelial cells and lung fibroblasts via FXR‐dependent and independent mechanisms.